The network approach to laboratory procurement and supply chain management: Addressing the system issues to enhance HIV viral load scale-up - Jason Williams; Dianna Edgil; Mathew Wattleworth; Clement Ndongmo; Joel Kuritsky (AOSIS, 2020)
Investment in viral load scale-up in order to control the HIV epidemic and meet the Joint United Nations Programme on HIV and AIDS (UNAIDS) '90-90-90' goals has prompted the President's Emergency Plan for AIDS Relief and countries to increase their investment in viral load and infant virological testing. This has resulted in the increased procurement of molecular-based instruments, with many countries having challenges to effectively procure and place these products. In response to these challenges, the global laboratory stakeholder community has developed an informed 'network approach' to guide placement strategies. This article defines and describes the 'network approach' for laboratory procurement and supply chain management to assist countries in developing a strategic instrument procurement and placement strategy. The four key pillars of the approach should be performed in a stepwise fashion, with regular reviews. The approach is comprised of (1) laboratory network optimisation, (2) forecasting and supply planning, (3) the development of effective procurement and strategic sourcing to develop 'all-inclusive' contracts that provide transparent pricing, and the establishment of clear service and maintenance expectations and key performance indicators and (4) performance management to increase communication and planning, and promote issue resolution. Investments in the network approach will enable countries to strengthen laboratory systems and ready them for future laboratory needs. These disease-agnostic networks will be poised to improve overall national disease surveillance and assist countries in responding to disease outbreaks and other chronic diseases.